Short-Term Humoral Immune Response of the pcDNA4-G Plasmid Expressing the Bovine Ephemeral Fever Virus G Gene in BALB/c Mice - Abayli, Hasan; Bulut, Hakan (Veterinaria Italiana, 2021)
Bovine ephemeral fever (BEF) is an arthropod‑borne viral disease characterised by a short‑term clinical expression that can lead to significant losses in high‑yielding cattle and water buffaloes. In this study, we aimed to generate a recombinant plasmid expressing the glycoprotein (G) of the BEF virus (BEFV) and to stimulate a humoral immune response to this protein in BALB / c mice immunised with the recombinant plasmid. Expression of the encoded protein was demonstrated by western blotting and immunoperoxidase tests. The suitable plasmids were intramuscularly administered to BALB/c mice on days 0, 14 and 21. The antibody response in the immunised mice was measured by a plaque reduction neutralization test (PRNT) and enzyme‑linked immunosorbent assay (ELISA). According to BEFV ELISA, only two of the seven animals in these groups exceeded the cut‑off value. A significant difference was observed in the mean OD values at 450 nm absorbance in the pcDNA4‑G‑immunised group when compared with those in the plasmid control group at 30 days (p < 0.05). According to PRNT50 results, a 1:20 (p < 0.05) antibody response was obtained at 30 days in pcDNA4‑G (100 μg)‑immunised mice, whereas this ratio was 1:80 (p < 0.001) in BEFV‑immunised mice (1,000 PFU/0.5 ml). We conclude that the humoral immune response was stimulated in experimental mice immunised with the recombinant plasmid. However, disappointingly, the antibody response was markedly low in pcDNA4‑G‑immunised mice.